Molecular Evidence of Bartonella melophagi in Ticks in Border Areas of Xinjiang, China - Ni, Jun; Ren, Qiaoyun; Lin, Hanliang; Aizezi, Malike; Luo, Jin; Luo, Yi; Ma, Zhan; Chen, Ze; Liu, Wenge; Guo, Junhui; Qu, Zhiqiang; Xu, Xiaofeng; et al. (Frontiers in Veterinary Science, 2021)
Bartonella are gram-negative intracellular bacteria; certain species of Bartonella can cause diseases in mammals and humans. Ticks play a major role in the transmission of Bartonella. Xinjiang is the largest province in China according to the land area and has one-third of the tick species in China; the infection rate of Bartonella in ticks in the Xinjiang border areas has not been studied in detail. Therefore, this study investigated the situation with tick infections by Bartonella in the Xinjiang border areas; the purpose of the study is tantamount to fill in the gaps in information on genetic diversity of tick infections by Bartonella in Xinjiang. We tested 1,549 tick samples from domestic animals (sheep and cattle) for Bartonella using ribC-PCR. Positive samples from ribC-PCR assay for Bartonella spp. were further submitted to PCR assays targeting the ITS, rpoB and gltA genes, followed by phylogenetic analyses. Bartonella DNA was detected in 2.19% (34/1549) tick samples, the ITS, rpoB and gltA genes of ribC gene-positive samples were amplified to identify nine samples of Bartonella melophagi. In this study, molecular analysis to assess the presence and the genetic diversity of B. melophagi in tick collected from sheep and cattle from Xinjiang, China. It provides new informations on the presence and identity of B. melophagi in ticks and in ticks from sheep and cattle.